The Use of Second Accounts Among Communication Science Students at Surabaya State University - Fitri Norhabiba (Universitas 17 Agustus 1945 Surabaya, 2025)
Digital transformation has shifted interpersonal communication patterns to digital spaces, raising concerns about social media's ability to replace intimate face-to-face communication. This study analyzes the effectiveness of social media platforms as a substitute for intimate communication using a quantitative approach through a questionnaire of 118 active users. The results reveal an intensive usage pattern (average 1-4 hours/day) with Instagram and WhatsApp as the dominant platforms. Primary motivations include entertainment (75.4%), communication (64.4%), and monitoring social activities (49.2%). Some 62.7% of respondents have a second account to manage their digital identity, primarily for privacy (37.8%) and self-expression (33.8%). Social media is considered effective as a substitute for intimate communication (average satisfaction score 8.3/10), with chat/DM features being the primary tool (72%). The most dominant reason for having a second account is privacy (37.8%), followed by self-expression (33.8%), and interaction with close friends (24.3%). These findings indicate that second accounts are used as more closed personal spaces, allowing users to express themselves freely without pressure from a public audience. The theory used is context collapse, where individuals face identity dilemmas in front of a heterogeneous audience. Creating a second account becomes an adaptive strategy to separate social contexts, manage privacy boundaries, and maintain a safer and more authentic space for expression. Keywords: second account, gen z, context collapse, social media, privacy